Early warning scores and trigger recommendations must be used with care in older home nursing care patients: Results from an observational study - Kristin Jeppestøl; Marit Kirkevold; Line K. Bragstad (Nursing Open, 2023)
Abstract Aims To explore modified early warning scores (MEWSs) and deviating vital signs among older home nursing care patients to determine whether the MEWS trigger recommendations were adhered to in cases of where registered nurses (RNs) suspected acute functional decline. Design Prospective observational study with a descriptive, explorative design. Methods Participants were included from April 2018 to February 2019. Demographic, health‐related and clinical data were collected over a 3‐month period. Results In all, 135 older patients participated. Median MEWS (n = 444) was 1 (interquartile range (IQR) 1–2). Frequently deviating vital signs were respiratory (88.8%) and heart rate (15.3%). Median habitual MEWS (n = 51) was 1 (IQR 0–1). Deviating vital signs were respiratory (72.5%) and heart rate (19.6%). A significant difference between habitual MEWS and MEWS recorded in cases of suspected functional decline was found (p = 0.002). MEWS' trigger recommendations were adhered to in 68.9% of all MEWS measurements.